Flow evaluation of a compliant coronary artery anastomosis model - Pedroso, Pedro D.; Venugopalan, Ramakrishna; Anayiotos, Andreas (My University, 2001)
A study was done on the flow evaluation of a compliant coronary artery anastomosis model. The models were constructed of a silicone elastomer having an inlet angle of 30 degrees with internal diameters of 5 mm (artery) and 7 mm (veins). The analysis showed the presence of secondary velocity components at downstream sections of the Coronary artery bypass grafting (CABG).
Keywords: Acoustic impedance; Cardiovascular system; Elastomers; Hemodynamics; Lithography